Advanced structural multimodal imaging of a patient with subcortical band heterotopia. Issue 3 (3rd October 2016) - Kini, Lohith G.; Nasrallah, Ilya M.; Coto, Carlos; Ferraro, Lindsay C.; Davis, Kathryn A.
Summary: Subcortical band heterotopia (SBH) is a disorder of neuronal migration most commonly due to mutations of the Doublecortin ( DCX ) gene. A range of phenotypes is seen, with most patients having some degree of epilepsy and intellectual disability. Advanced diffusion and structural magnetic resonance imaging (MRI) sequences may be useful in identifying heterotopias and dysplasias of different sizes in drug‐resistant epilepsy. We describe a patient with SBH and drug‐resistant epilepsy and investigate neurite density, neurite dispersion, and diffusion parameters as compared to a healthy control through the use of multiple advanced MRI modalities. Neurite density and dispersion in heterotopia was found to be more similar to white matter than to gray matter. Neurite density and dispersion maps obtained using diffusion imaging may be able to better characterize different subtypes of heterotopia.